Allelism of the mutants ovc and cut of Neurospora crassa - C. W. Banks; S. N. Bennett; W. A. Krissinger (Fungal Genetics Reports, 1997)
The mutant overaccumulator of carotenoids, ovc, which we obtained from the Fungal Genetics Stock Center, had been reported by Harding, et al. (1984 Neurospora Newsl. 31:23-25) to be in the right arm of LG IV between col-4and met-5. Examination of ovc in our laboratory revealed that in addition to having increased pigmentation, ovc was also osmotic sensitive and allelic to cut.